Study and identification of the active chemical compounds present in the alcoholic extracts of the Ephedra plant, E.campylopoda, in Lattakia, Bahlouliyeh region. (Latakia University Journal -Biological Sciences Series, 2024)
The aim of this study is to detect the active chemical compounds present in the alcoholic extract (ethanolic and methanolic) of the Ephedra plant, E. campylopoda, from the Ephedraceae family, and to compare the two extracts in view of its high medical importance and widespread use, especially after the spread of the story of a Palestinian shepherd who He was cured of cancer after using it.Phytochemical analysis showed that the alcoholic extract contains many bioactive compounds, including terpenes, alkaloids, sterols, carboxylic acids, etc. An estimated 36 metabolites were identified in the ethanolic extract, and 66 metabolites were identified in the methanol extract. The methanol extract was more effective than the ethanolic extract, as the percentage of aromatic compounds, alkaloids, phenols, and ketones was higher. That is, methanol has been shown to be an effective solvent for the extraction of various plant secondary metabolites.The results also indicated that fatty acids, especially palmitic acid, carbohydrates, and sitosterols constitute the majority of metabolites in the ethanolic extract of E. campylopoda. While aromatic compounds and alkaloids constitute the majority of metabolites in methanol, the qualitative examination of plant metabolites showed that the methanol extract contains a greater number and diversity than ethanol. Finally, these results confirm the presence of various biologically active metabolites, which give lentils high importance at the medical level.